Pressure Related Ocular Parameters in Caucasian Patients with Primary Open-Angle Glaucoma - Galina, Dimitrova; Antonela, Ljubic; Biljana, Tojtovska; Keti, Tagasovska; Urosh, Tomasevic (Journal of Ocular Diseases and Therapeutics, 2021)
Objectives: To investigate pressure related ocular parameters (intraocular pressure (IOP), estimated trans-lamina cribrosa pressure difference (TLPD) and ocular perfusion pressure (OPP) in Caucasian patients with primary open angle glaucoma (POAG) and control subjects. Methods: This is an observational cross-section study that included 57 subjects (27 patients with open-angle glaucoma and 30 healthy control subjects). All subjects underwent ophthalmic and systemic measurements in order to evaluate pressure related ocular parameters – IOP (mmHg), OPP (mmHg), and TLPD (mmHg) based on established formulas. The differences in the IOP, OPP and TLPD values between patients with POAG and control subjects were evaluated. Results: Intraocular pressure and TLPD were significantly higher in patients with glaucoma (mean IOP= 18.93 ± 4.53 mmHg; TLPD= 9.47 ± 5.02 mmHg), than in control subjects (IOP= 16.47 ± 2.60 mmHg; TLPD= 6.82 ± 3.60 mmHg) (p=0.017 and p=0.025 respectively). In univariate logistic progression, IOP and TLPD were significant predictors for POAG. Conclusion: Our results suggest that in addition to IOP, TLPD is also significantly higher in Caucasian patients with POAG than in control subjects and both parameters are significant predictors of POAG. This suggests that TLPD may have a role in the pathogenesis of POAG.